Analisis Volume Ekspor CPO Indonesia ke India melalui Pendekatan Error Correction Model - Khoirudin, Rifki; Yuniarto, Arif Sapta; Khasanah, Uswatun (Jurnal Samudra Ekonomi dan Bisnis, 2024)
Palm Oil (CPO) is one of the export products that has the largest contribution in Indonesia, where India is the export destination country. This research aims to analyze the factors that influence the volume of Indonesian CPO exports to India. This research uses secondary time series data, namely annual data for the period 1990 to 2021, and is analyzed using the Error Correction Model (ECM) method. The results show that in the short and long term, world CPO prices and GDP per capita have a positive and significant effect on the volume of Indonesian CPO exports to India. Meanwhile, in the short term, the CPO production variable has a positive and significant effect on export volume. The exchange rate and domestic CPO prices do not have a significant effect in the short or long term.